Implementation and Testing of Cisco IP SLA in Smart Grid Environments - Horálek, Josef; Holík, Filip; Hurtová, Veronika (IEEE (Institute of Electrical and Electronics Engineers), 2017)
Smart grid networks are becoming more and more commonly deployed due to their undisputed benefits. On the other hand, there is a high demand for reliability and functionality of these networks. This paper is analysing usage of the IP SLA for monitoring network state and collecting important information for potential problem detection and solving. The practical part of the paper presents implementation of the IP SLA into the smart grid network environment and its testing. The results from several simulated scenarios with different QoS classes, used within the smart grid networks, are discussed.
Implementace a testování Cisco IP SLA v prostředí Smart Grid sítí
Keywords: Cisco IP SLA; network testing; Smart Grid; QoS; Cisco IP SLA; testování sítě; Smart Grid; QoS